2015
DOI: 10.1021/acs.joc.5b00969
|View full text |Cite
|
Sign up to set email alerts
|

α-Hydroxy and α-Oxo Selenoamides: Synthesis via Nucleophilic Selenocarbamoylation of Carbonyl Compounds and Characterization

Abstract: Carbonyl compounds were added to selenocarbamoyllithiums to generate α-hydroxy and α-oxo selenoamides. Their conformations were determined by X-ray analyses. These compounds adopted conformations that were almost identical to those of ordinary amides. Unlike the consistency of the chemical shifts of the C═Se groups of the selenoamides in (13)C NMR spectra and the (1)J coupling constants of the C═Se groups, the substituents far from the selenium atom influenced the chemical shifts in (77)Se NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 88 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…For example, Murai and co‐workers reported the synthesis of α‐hydroxy and α‐oxoselenoamides via nucleophilic selenocarbamoylation of carbonyl compounds (Scheme 4). [79] In the substrate scope evaluation, the authors observed a significant selenium‐77 chemical shift range in the synthesized compounds, according to the substituent groups. They have demonstrated the basic NMR properties of selenocarbonyl compounds, which is an important knowledge for the organic synthetic chemists.…”
Section: Se Nmr Spectroscopy In Organic Synthesismentioning
confidence: 99%
“…For example, Murai and co‐workers reported the synthesis of α‐hydroxy and α‐oxoselenoamides via nucleophilic selenocarbamoylation of carbonyl compounds (Scheme 4). [79] In the substrate scope evaluation, the authors observed a significant selenium‐77 chemical shift range in the synthesized compounds, according to the substituent groups. They have demonstrated the basic NMR properties of selenocarbonyl compounds, which is an important knowledge for the organic synthetic chemists.…”
Section: Se Nmr Spectroscopy In Organic Synthesismentioning
confidence: 99%
“…In particular, α‐oxo‐ and α‐hydroxy‐ selenoamides of formula 77 and 78 a are not so common molecules but they can be synthesized straightforwardly as illustrated in Scheme 18. In this sense, these selenoamides can be prepared starting from N , N ‐dibenzyl selenoformamide ( 79 ) by treatment with lithium diisopropylamide [113] via the selenocarbamoyllithium intermediate 80 [114] . In addition, α‐oxoselenoamides of formula 78 can also be prepared from aryl methyl ketones such as 81 and amines employing selenium dioxide as selenium source.…”
Section: Chemistrymentioning
confidence: 99%
“…In this sense, these selenoamides can be prepared starting from N,N-dibenzyl selenoformamide (79) by treatment with lithium diisopropylamide [113] via the selenocarbamoyllithium intermediate 80. [114] In addition, α-oxoselenoamides of formula 78 can also be prepared from aryl methyl ketones such as 81 and amines employing selenium dioxide as selenium source. This method is a simple and direct approach to access these α-oxoselenium derivatives obtained under very mild conditions.…”
Section: Selenoesters α-Seleno Ketones and Othersmentioning
confidence: 99%
“…In contrast, there is little information available regarding efficient methods for the preparation of phosphorus compounds with both central and axial chirality. In this regard, we have developed a synthesis of phosphorus compounds having both central chirality of a phosphorus atom and axial chirality of a binaphthyl group (Scheme ) during our studies on organochalcogen compounds . We obtained P ‐stereogenic phosphinates II and phosphonothioic acids IV with a binaphthyl group with high diastereoselectivities by reacting phosphonates I and phosphonothioates III with Grignard reagents and metal hydroxides while transferring the axial chirality of the binaphthyl group to the central chirality of the phosphorus atom.…”
Section: Introductionmentioning
confidence: 99%